(3ebGeGJ HOjY GdReGf GdgePGfjs - (3HOjY GdReGf GdgePGfj , CMeO Hf GdMSjf Hf jMji GdgePGfj, CHh GdaVd,J (B398 (3g` s
(3ChdgG (B:s
(3GdChdi bGd(B: (3MOKfj YjSi Hf gTGe bGd(B: (3LeYJfj eY Qabg hdjeg GdKGfjI(B: (3hef EfTGA GdHOjY aj ebGeGJ GdEScfOQj bGd s
(3BNQgG (B:s
(3GdChdi(B: (3hGfKGdJ GdUdGJ Ydjg hbdJ deG JBfSfG ef Cjf eWdY gPG GdHOQ GdKGfjI(B: (3CdSJ CHG GdaJM GdCScfOQj JWha aj GdCShGb s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GfXQ GdLRA GdChd Qbe (B790 (3COHs
(3ebGeJGf(B: (3GdChdi JJYdb HPcQ GdLGMXs
(3hhQO CjVkG JMJ Qbe (B474(3, (B2177s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B115 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B209s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B73 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1785s
Keywords: (3GdCOHs